2014
DOI: 10.1080/07399332.2014.943840
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Domestic Violence and HIV Serostatus Among Married and Formerly Married Women in Kenya

Abstract: The prevalence of both domestic violence (DV) and HIV among Kenyan women is known to be high, but the relationship between them is unknown. Nationally representative cross-sectional data from married and formerly married (MFM) women responding to the Kenya Demographic and Health Survey 2008/2009 were analyzed adjusting for complex survey design. Multivariable logistic regressions were used to assess the covariate-adjusted associations between HIV serostatus and any reported DV as well as four constituent DV me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
(138 reference statements)
0
12
1
Order By: Relevance
“…The prevalence of sexual violence was 74.8% in our study, a figure much higher than reported from developed and developing countries (20,23,31,32). A meta-analysis in the United States of America showed the prevalence of intimate partner violence was 55.3% in HIV-positive women, and 30% of these women had experienced posttraumatic stress disorder (32).…”
Section: Discussioncontrasting
confidence: 61%
“…The prevalence of sexual violence was 74.8% in our study, a figure much higher than reported from developed and developing countries (20,23,31,32). A meta-analysis in the United States of America showed the prevalence of intimate partner violence was 55.3% in HIV-positive women, and 30% of these women had experienced posttraumatic stress disorder (32).…”
Section: Discussioncontrasting
confidence: 61%
“…In this study, control over the participants' lives even included personal tasks such as medication and self-care behaviours so that some husbands prevented their wives from receiving care and adhering to medication, and this might impair women's health and contribute to disease progression. Previous studies have revealed that men's interference with women's health care is one of the manifestations of violence against HIV-infected women (Lichtenstein, 2006;Kouyoumdjian et al, 2013) and the adverse consequences of violence are worse in these women due to their lack of access to medical care (Onsomu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…T. Montgomery et al, 2012). Findings from the parent study cohort, published elsewhere (Ngure et al, 2014), reveal a similar dynamic in childbearing decisions; when men wanted a child but their wives did not, they used language such as “she must” and “I will force her.” Such intense divisions of power have been known to result in domestic violence against women (Pintye et al, 2015; Wingood & DiClemente, 2000), and HIV seropositive women are at higher risk of such abuse than their seronegative peers in both Kenya (Fonck et al, 2005; Onsomu et al, 2014) and Uganda (Emusu et al, 2009; Were et al, 2011). These patterns provide a possible explanation for why the seropositive men in this study were vocal about their control of household decisions and silent about the potential for taking PrEP to be burdensome to their spouses: they may experience their HIV diagnosis as a loss of masculine control, which they are subsequently attempting to re-establish in their homes.…”
Section: Discussionmentioning
confidence: 99%